Factors associated with subjective state of health in college students - Rezapour, Mahdi (Frontiers in Psychology, 2022)
Although the COVID-19 pandemic has been deeply painful, it has provided a rare opportunity to study the behavioral responses of individuals in adapting to an unprecedented life event. An analysis of participants’ subjective health ratings during the COVID-19 pandemic was conducted by utilizing data from a survey of college students across seven universities in the USA. In this study, we challenge the unidimensional factors to the subjective well-being by considering all multiplicative associations of those factors. Considering the interaction terms are especially important as not considering the possible multiplicative impacts of variables might obscure our understanding regarding the real associations. Results indicated that subjective health during the pandemic is multidimensional and associated with demographic and individual characteristics of students (e.g., self-reported body mass index (BMI)), various negative emotions (e.g., sadness, irritability), and health-related behaviors (e.g., exercise). For instance, it was found that the association between screen hours and subjective well-being is interactive, with a better subjective health of students with higher family income. Or the association between being afraid and subjective health varies based on students’ BMI. Implications for future research and policies are discussed.